The euro exchange rate during the European sovereign debt crisis - dancing to its own tune? - Michael Ehrmann; Chiara Osbat; Jan Stráský; Lenno Uusküla (European Central Bank (ECB), 2013)
This paper studies the determinants of the euro exchange rate during the European sovereign debt crisis, allowing a role for macroeconomic fundamentals, policy actions and the public debate by policy makers. It finds that the euro exchange rate mainly danced to its own tune, with a particularly low explanatory power for macroeconomic fundamentals. Among the few factors that are found to have affected changes in exchanges rate levels are policy actions at the EU level and by the ECB. The findings of the paper also suggest that financial markets might have been less reactive to the public debate by policy makers than previously feared. Still, there are instances where exchange rate volatility was increasing in response to news, such as on days when several politicians from AAA-rated countries went public with negative statements, suggesting that communication by policy makers at times of crisis should be cautious about triggering undesirable financial market reactions.
Keywords: E52; E62; F31; F42; G14; 330; announcements; Exchange Rates; fundamentals; sovereign debt crisis